Stability of magnetosonic waves in an anti-loss cone plasma - Venugopal, C.; George, S.; Rajeev, V.R.; Kurian, M.J.; Anilkumar, C.P.; Jayapal, R. (My University, 2013)
We have studied the stability of magnetosonic wave in a plasma, where the ions and electrons are described by anti-loss cone (ALC) distributions. Our studies indicate that the magnetosonic waves produced by ions and electrons with ALC distributions are in the higher frequency end within the range of frequencies, as observed by the Combined Release and Radiation Effects Satellite spacecraft. They are weakly damped and can, therefore, travel long distances. These waves are expected to play an important role in the acceleration of radiation belt electrons.
Keywords: Magnetosonic wave; Dispersion relation; Anti-loss cone plasma; Radiation belt electrons; Stability